The effect of calcium hydroxide and double antibiotic paste on radiographic outcomes and periapical MMP-8 levels in regenerative endodontic procedures: a randomized clinical trial - Burc PEKPINARLI; Mehmet Emin KAVAL; Dilsah COGULU; Betul ILHAN; Timo SORSA; Taina TERVAHARTIALA; Ozant ONCAG (University of São Paulo, 2024)
Abstract In children with poor oral hygiene, dental caries are the most common factor that causes periapical pathologies as a result of irreversible pulpal injuries and leads to the cessation of root development in immature permanent molar teeth. Objective The primary goal is to evaluate the effects of two different intracanal medicaments, calcium hydroxide [Ca(OH)2] and double antibiotic paste (DAP), on radiographic outcomes during regenerative endodontic procedures (REP) of immature permanent mandibular first molars with symptomatic irreversible pulpitis and symptomatic apical periodontitis (SIP/SAP). Additionally, the secondary goal was to evaluate MMP-8 levels during REP using two different intracanal medicaments. Methodology The study included 20 patients with immature mandibular first molars exhibiting SIP/SAP. Participants were randomly assigned into two groups based on the applied intracanal medicament. Ca(OH)2 (n=10) was prepared by mixing it with sterile distilled water, while the same amount of powdered metronidazole and ciprofloxacin were mixed and combined with sterile distilled water for DAP (n=10). MMP-8 in periapical samples were measured at baseline and on the 14th day using immunofluorometric assay. Image-J software with TurboReg plug-in was utilized to determine changes in root length, root width, radiographic root area (RRA) during the 12-month follow-up period. Data were analyzed by SPSS 25.0 (p<.05). Results Significant increase in MMP-8 on the 14th day compared to baseline in both groups (p<0.001). There was no significant difference between the two groups in terms of the increase in MMP-8 (p>0.05). Root length significantly increased in both groups (p=0.001), with Ca(OH)2 showing a greater increase (p=0.046). Root width and RRA increased similarly in both groups at 12th month. Conclusion Both Ca(OH)2 and DAP applications resulted in a significant increase in periapical MMP-8 levels. Increase in radiographic root width and root area was similar between two groups, but Ca(OH)2 led to a significantly greater increase in root length. Further studies with larger sample sizes are necessary to validate our findings during REP of vital immature permanent mandibular molars. Clinical Trials database: NCT05581706